Investigation of impacted supernumerary teeth: A cone beam computed tomograph (CBCT) study - Gürler, Gökhan; Delilbaşı, Barış Çağrı; Delilbaşı, Evren (My University, 2017)
The purpose of this study was to investigate the impacted supernumerary teeth which were initially detected on panoramic radiographs by using cone beam computed tomography (CBCT).Materials and Methods_ In this retrospective study, supernumerary teeth diagnosed on panoramic radiographs taken from patients who had admitted for routine dental treatment were evaluated using CBCT. Patients’ age, gender, systemic conditions as well as number of supernumerary teeth, unilateral-bilateral presence, anatomical localization (maxilla, mandible, anterior-premolar-molar, mesiodenslateral-canine, parapremolar-paramolar-distomolar) shape (rudimentary, supplemental, tuberculate, odontoma), position (palatal-lingual-buccal-labial-central), shortest distance between the tooth and adjacent cortical plate, complications and treatment were assessed. Results_ A total of 47 impacted supernumerary teeth in 34 patients were investigated in this study. Of these, 33 (70.2%) were unilateral and 14 (29.8%) were bilateral. Only 1 supernumerary tooth was found in 27 patients (79.4%) whereas 7 patients (20.6%) had 2 or more supernumerary teeth. Most of the teeth located in the anterior region (74.4%) of the jaws and maxilla (74.4%). Twenty teeth (42.5%) were mesiodens, 11 (23.4%) were lateral or canine, 14 (29.7%) were parapremolar and 2(4.4%) were distomolar. Twentyseven teeth (57.4%) were rudimentary, 15 (31.9%) were supplemental and 5 (10.7%) were odontoma in shape. The shortest distance between the supernumerary tooth and adjacent cortical plate varied between 0 to 2.5 mm with a mean of 0.66 mm. The most common clinical complaint was the non-eruption of permanent teeth (42.5%). All supernumerary teeth were removed under local anesthesia. Orthodontic traction was performed for those impacted permanent teeth if necessary. Conclusion_ Impacted supernumerary teeth are usually in close proximity to cortical bone. Although this may facilitate surgical access, there is a risk of damaging surrounding anatomical structures. Therefore, CBCT evaluation of impacted supernumerary teeth for accurate planning is recommended.

Amaç: Bu çalışmanın amacı ilk olarak panoramik radyografilerde fark edilen gömülü süpernümerer dişlerin konik ışınlı bilgisayarlı tomografiyle (CBCT) incelenmesidir. Gereç ve Yöntem: Bu retrospektif çalışmada, rutin dental muayene amacıyla panoramik radyografi çekilen hastalarda tespit edilen süpernümerer dişler CBCT ile incelendi. Hastaların yaş, cinsiyet, sistemik durumları ile süpernümerer diş sayısı, tek-çift taraflı oluşu, anatomik lokalizasyonu (maksilla, mandibula, anterior- premolar molar, meziodens- lateral, kanin-parapremolar- paramolardistomolar), şekli (rudumenter, suplemetal, tüberküleyt, odontoma), pozisyonu (palatinal- lingual- bukkal- labialorta hat), süpernümerer dişin komşu kortekse olan uzaklığı, yol açtığı sorunlar ve tedavi yaklaşımları değerlendirildi. Bulgular: 34 hastada tespit edilen 47 adet süpernümerer diş incelendi. Bu dişlerden 33'ü (%70.2) unilateral, 14'ü (29.8%) bilateraldi. Yirmi yedi (79.4%) hastada sadece 1 süpernümere diş mevcutken, 7 (%20.6) hastada 2 veya daha fazla diş mevcuttu. Dişlerin çoğu çenelerin anterior bölgesinde (%74.4) ve maksillada (%74.4) lokalizeydi. Yirmi bir (%44.6) diş meziyodens, 11 (%21.4) diş lateral ya da kanin, 14 diş (%29.7) parapremolar, ve 1 (%2.3) diş distomolar olarak tespit edildi. Yirmi yedi diş (%57.4) rudimenter, 15 diş (%31.9) suplemental, 5 diş (%10.7) odontoma şeklindeydi. Süpernümerer dişin komşu kortekse olan mesafesi 0 ile 2.5 mm arasında (ortalama 0.66 mm) ölçüldü. Bütün süpernümerer dişler lokal anesteziyle cerrahi olarak çıkartıldı. Gereken olgularda ortodontik tedavi uygulandı. Sonuç: Gömülü süpernümerer dişler komşu kortikal tabakaya yakın konumlanmaktadırlar. Bu durum cerrahi girişi kolaylaştırmasına rağmen, çevre anatomik yapıları ve dişlere zarar verme riski vardır. Bu nedenle doğru planlama yapabilmek için gömülü süpernümere dişlerin CBCT ile incelenmesi önerilmektedir.
Gömülü süpernümerer dişlerin incelenmesi: Bir konik ışınlı bilgisayarlı tomografi (KIBT) çalışması
Keywords: Supernumerary Tooth; Hyperdontia; CBCT; Impacted Teeth; Cortical Bone; Süpernümerer Diş; Hiperdonti; CBCT; Gömük Diş; Kortikal Kemik